Open access on a zero budget: a case study of Postcolonial Text - John Willinsky; Ranjini Mendis (Information Research: An International Electronic Journal)
Introduction. The founding of a new open access journal is described in terms of its use of the open source software Open Journal Systems, its contribution to a new field of inquiry and its ability to operate on a zero budget in terms of regular expenses. Method. A case study method is deployed describing the circumstances of the journal's founding and current manner of publishing. Analysis. The use of online and open source software, as well as a global team of volunteers is presented as the basis of sustaining an open access approach to publishing. Results. The journal has been able to operate with a zero dollar operating budget over the course of its first six issues and is in a position to continue in this manner. Conclusion. . A strong commitment to the principles of developing a new field of inquiry committed to global issues of access to knowledge, in combination with open source and Internet technologies, has lowered the barriers to the exercise of academic freedom on a modest, but nonetheless global scale.